Developing Information Services for Visually-Impaired Students in Indonesia - E. Variant Anna, Nove; Dessy Harisanty, Dessy; Puspitasari Srirahayu, Dyah; Endang Fitriyah Mannan, Endang; Sua’daa Irfana, Maisyatus (International Journal of Engineering and Technology, 2018)
This study aims to acknowledge the information needed by visually-impaired students in Indonesia. The results of this study will be used as a basis to develop library services that can be useful for visually-impaired students. The research was conducted in Foundation for Blind Handicapped Persons (YPAB) in Surabaya and involved 30 visually-impaired students ranging from 11-20 years of age. The research was conducted using questionnaires and interviews at YPAB. From the results it can be known that all students regularly visit the library 1-4 times a week, they know about the library services in the school from the teachers and the most widely used service is the general collection service in braille format. The most frequent activities done by students are chatting and discussing, whereas browsing is rarely because there is no internet connection and the number of computers is limited. Information available in the library includes information for completing schoolwork and fiction books in the form of braille. The recommendations from research results include: improving information services through teacher librarians and provide information and internet literacy training for students and teachers.